The Philippine address the future of a GIS-based address system through scenario building and strategic prospectives - Ocampo, Elaine B. (University of the Philippines Diliman, 2011)
An address is an important element in our day to day lives. Most operations of businesses other organization hinges on having the correct address information. Address management is a very important function of the local government units that is often overlooked. Managing addresses has always been a problem in the Philippines. But with the advancement of information and spatial technologies (i.e. geographical information system), this problem is expected to be resolved. This project was done as a preliminary study for planning an addressing initiative for the Philippines. This project reviewed address standards and practices currently implemented in the Philippines and in other countries and at the same time examined the variables that would affect any addressing initiative in the Philippines. The possible futures of using GIS in managing the address system of the different localities in the country is also explored using the scenario building process. At the end of this paper, the project findings were used as basis for formulating recommendations that can serve as inputs to planning an addressing initiative for the Philippines.